A Novel Insight Into the Fate of Cardiomyocytes in Ischemia-Reperfusion Injury: From Iron Metabolism to Ferroptosis - Li, Jing-yan; Liu, Shuang-qing; Yao, Ren-qi; Tian, Ying-ping; Yao, Yong-ming (Frontiers in Cell and Developmental Biology, 2021)
Ischemia-reperfusion injury (IRI), critically involved in the pathology of reperfusion therapy for myocardial infarction, is closely related to oxidative stress the inflammatory response, and disturbances in energy metabolism. Emerging evidence shows that metabolic imbalances of iron participate in the pathophysiological process of cardiomyocyte IRI [also termed as myocardial ischemia-reperfusion injury (MIRI)]. Iron is an essential mineral required for vital physiological functions, including cellular respiration, lipid and oxygen metabolism, and protein synthesis. Nevertheless, cardiomyocyte homeostasis and viability are inclined to be jeopardized by iron-induced toxicity under pathological conditions, which is defined as ferroptosis. Upon the occurrence of IRI, excessive iron is transported into cells that drive cardiomyocytes more vulnerable to ferroptosis by the accumulation of reactive oxygen species (ROS) through Fenton reaction and Haber–Weiss reaction. The increased ROS production in ferroptosis correspondingly leads cardiomyocytes to become more sensitive to oxidative stress under the exposure of excess iron. Therefore, ferroptosis might play an important role in the pathogenic progression of MIRI, and precisely targeting ferroptosis mechanisms may be a promising therapeutic option to revert myocardial remodeling. Notably, targeting inhibitors are expected to prevent MIRI deterioration by suppressing cardiomyocyte ferroptosis. Here, we review the pathophysiological alterations from iron homeostasis to ferroptosis together with potential pathways regarding ferroptosis secondary to cardiovascular IRI. We also provide a comprehensive analysis of ferroptosis inhibitors and initiators, as well as regulatory genes involved in the setting of MIRI.